How does displacement of albumin-bound tryptophan cause sustained increases in the free tryptophan concentration in plasma and 5-hydroxytryptamine synthesis in brain? - Salter, M (1989)
Models of tryptophan catabolism and binding to serum albumin are presented to explain the observed effect of displacement of tryptophan from albumin on the concentrations of free and bound tryptophan and on the rate of 5-hydroxytryptamine (5-HT) synthesis from tryptophan in the brain. A rapid rate of dissociation of tryptophan from albumin (compared to the transit time of tryptophan through the liver) and a large fractional extraction of the free pool of tryptophan during passage through the liver are shown to be necessary factors in determining the effects observed. Because of the low fractional extraction of free tryptophan in the brain, the synthesis of 5-HT will be dependent only upon the free pool of tryptophan. Dissociation of tryptophan from albumin only causes a sustained increase in 5-HT synthesis in the brain because of the effect that this dissociation has on hepatic tryptophan catabolism and thereby on the free pool of tryptophan.